It is finally time for adjuvant therapy in melanoma. (September 2018) - Napolitano, S.; Brancaccio, G.; Argenziano, G.; Martinelli, E.; Morgillo, F.; Ciardiello, F.; Troiani, T.
Highlights: Stage II C as well as stage III melanoma patients may deserve adjuvant therapy. Until recently, IFNα has been the only approved drug for the treatment of adjuvant melanoma, with unclear overall survival benefit. There was no evidence that the benefit of IFNα differed in different patient types, except for the ones with ulceration. Considering the toxic effects and the cost of the treatment, the use of ipilimumab in the adjuvant setting is quite controversial. The results from the latest trials with immunotherapy (PD-1 inhibitors) and molecular targeted therapy have revolutionized the management of adjuvant treatment for melanoma. Abstract: Although melanoma is amenable to early detection, there has been no decline in the mortality rate of this disease and the prognosis of patients with high-risk primary melanoma or with macroscopic nodal involvement remains poor. The best option for patients with higher-risk melanoma is to receive effective adjuvant therapy in order to reduce their chances of recurrence. Multiple systemic therapeutic agents have been tested as adjuvant therapy for melanoma with durable benefits seen only with interferon- to date. More recently ipilimumab at the high dose of 10 mg/kg has shown a significant improvement in terms of Relapse free survival and Overall survival for stage III melanoma patients but at a significant cost in terms of immune-related toxicities. More recently, novel treatment options have emerged. The results from the latest trials with immunotherapy (PD-1 inhibitors) and molecular targeted therapy (BRAF inhibitor + MEK inhibitor) have revolutionized the management of adjuvant treatment for melanoma. As the results from these trials will mature in the next years, a change in the landscape of adjuvant treatment for melanoma is expected, resulting in new challenges in treatment decisions such as optimizing patients' selection through predictive and prognostic biomarkers, and management of treatment related adverse events, in particular immune related toxicities.